Robust stability of systems with delay - Mustafaeva, R.; Khusainov, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider linear stationary systems of differential equations with delay. The matrices that determine the dynamics of a system vary within a certain interval. We obtain sufficient conditions for the robust stability of systems uniform with respect to delay and depending on the deviation of the argument.